Exploring Teachers' Knowledge and Practices of Self-Regulated Learning: A Case Study in China - Fengmei, Zou (English Language Teaching Perspectives, 2023)
This paper reports the knowledge and practice of self-regulation of English teachers in public primary and secondary schools in South-East China. The data were collected from multiple classroom observations of and in-depth interviews with two English language teachers working in Chinese schools. This study reported that despite limited knowledge of Self-regulated learning teachers’ classroom practices reflected an extensive use of SRL strategies positively impacting students’ learning engagment. However, the workload and the traditional grade-focused assessment systems influenced teachers’ consideration of self and their students’ learning motivation, metacognition, and cognition. These findings indicate a need to strengthen English teachers’ metacognition, cognition and motivational-emotional regulation to support student learning.